Psychosocial development of women: Linking this literature to the study of leadership - Rosemary S. Caffarella; Bruce G. Barnett (Adult Education Research Conference, 1993)
Provided in this paper is an overview of the themes and a critique that emerged from a critical review of the literature on the psychosocial development of women, and an exploration of how these themes are linked to the theory of leadership. Observations are made for further research related to leadership in education.